Nitrogen sources alter ligninase and cellulase activities of thermophilic fungi isolated from compost and vermicompost - Ansari, Saeideh; Aliasgharzad, Nasser; Sarikhani, Mohammad Reza; Najafi, Nosratollah; Arzanlou, Mahdi; Ölmez, Fatih (Folia microbiologica, 2024)
Fungi harboring lignocellulolytic activity accelerate the composting process of agricultural wastes; however, using thermophilic fungal isolates for this process has been paid little attention. Moreover, exogenous nitrogen sources may differently affect fungal lignocellulolytic activity. A total of 250 thermophilic fungi were isolated from local compost and vermicompost samples. First, the isolates were qualitative assayed for ligninase and cellulase activities using Congo red (CR) and carboxymethyl cellulose (CMC) as substrates, respectively. Then, twenty superior isolates harboring higher ligninase and cellulase activities were selected and quantitatively assayed for both enzymes in basic mineral (BM) liquid medium supplemented with the relevant substrates and nitrogen sources including (NH4)2SO4 (AS), NH4NO3 (AN), urea (U), AS + U (1:1), or AN + U (1:1) with final nitrogen concentration of 0.3 g/L. The highest ligninase activities of 99.94, 89.82, 95.42, 96.25, and 98.34% of CR decolorization were recorded in isolates VC85, VC94, VC85, C145, and VC85 in the presence of AS, U, AS + U, AN, and AN + U, respectively. Mean ligninase activity of 63.75% in superior isolates was achieved in the presence of AS and ranked the highest among other N compounds. The isolates C200 and C184 exhibited the highest cellulolytic activity in the presence of AS and AN + U by 8.8 and 6.5 U/ml, respectively. Mean cellulase activity of 3.90 U/mL was achieved in AN + U and ranked the highest among other N compounds. Molecular identification of twenty superior isolates confirmed that all of them are belonging to Aspergillus fumigatus group. Focusing on the highest ligninase activity of the isolate VC85 in the presence of AS, the combination can be recommended as a potential bio-accelerator for compost production.
Keywords: Composting; kompostování; houby; Oxygenases; Nitrogen; dusík; Fungi; celulasa; Cellulase; oxygenasy